Nalar Hukum M. Quraish Shihab (Kajian Atas Ayat-ayat dalam Perkawinan di Dalam Tafsir Al-Misbah) - Ishaq, Zamroni (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
M. Quraish Shihab is a figure who has a special place among researchers of Al-Qur'an interpretation in Indonesia, even his thoughts regarding women and family earned him an honorary star from the Egyptian government, but since M. Quraish Shihab sparked related thoughts the law on saying Merry Christmas, the law on making and displaying statues, and wearing the hijab for Muslim women and other thoughts, many scholars, commentators and intellectuals in Indonesia criticized him, some even argued that he had left the ranks of the ulama. This article attempts to discuss M. Quraish Shihab's interpretation regarding the marriage verses in the al-Misbah commentary and the legal reasoning used therein. The ijtihad approach contained in the Ushul Fiqh science section is used in this research to answer the problem formulation, including the following; what is the form of the ijtihad method, and the legal characteristics that arise from this interpretation. The results of this research are; Firstly, the methods used are ijtihad intiqai, ijtihad bayani, and ijtihad al-jami' baina al- intiqai wa al-inshai. Second, the ease of implementing the laws mentioned, avoiding excessive forms of fanaticism, stimulating the reader's awareness in implementing the messages and laws that have been explained.